ADVERSITY QUOTIENT DITINJAU DARI SELF-EFFICACY PADA SISWA SMP X DI PEKALONGAN - Warhana, Arradhika; Arum Permitasari, I Rheny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2025)
This study aims to test whether there is a relationship between self-efficacy and adversity quotient in students of SMP X Pekalongan. The hypothesis put forward in this study is